Analisis Struktur Modal Perbankan Syariah di Indonesia - Mila Istiqamah; Supriyanto Supriyanto (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2017)
This study aims to analyze the factors that affect the sharia or Islamic banking capital structure in Indonesia during the period of 2011-2015. This research uses quarterly time series data which is analyzed by multiple regressions. The sample used in this research is 8 sharia banks in Indonesia and chosen by purposive sampling. The independent variables in this research are company size, growth rate, income stability and asset structure. And the dependent variable in this research is capital structure. Analyzer used is multiple linear regressions analysis. The results showed that company size, growth rate, sales stability and asset structure had significant effect on capital structure, and F test result showed that company size, growth rate, income stability and asset structure variables together influence capital structure. Based on the results of this study, it can be concluded that the factors considered by banks in determining the capital structure is the composition of assets and revenues earned. Therefore, sharia banking in Indonesia needs to optimize the revenue and total assets owned.